Pertumbuhan Legume pada Ketinggian yang Berbeda Growth of Legums in Different Altitude - Sarmita, Fitriani -; Hastuti, Endah Dwi; Haryanti, Sri - (Bioma : Berkala Ilmiah Biologi, 2011)
Alfalfa (Medicago sativa L.) was one of the example plant that the chlorophyll has been used for medicine,but there were obstacles in cultivation alfalfa (M. sativa L.), becouse the seed must have been imported. Besides that,in Indonesia Alfalfa’s seed was sterile. Legume used in this research will use as chlorophyll alternative source besidealfalfa (M. sativa L.). Legume that have been examined were planted in three location with different altitude that wasSemarang (200 m above sea level), Ungaran (316 m above sea level) and Bandungan (843 m above sea level).Alfalfa (M. sativa L.) is subtropical plant meanwhile legume used to be cultivated in Indonesia is tropical plant.That’s why in this research examined legume were planted in different altitude. Purposes of this research were toknow the growth of legume, knowing if there were interaction among five legumes and planting location withdifferent altitude.. Legumes that were used winged bean (Psophocarpus tetragonolobus (L.) DC.), cowpea (Vignaunguiculata (L.), alfalfa (M. sativa L.), long bean (Vigna sesquipedalis) and common bean (Phaseolus vulgaris L.).The experimental design is completely randomize design with four replication. The data were analyzed by ANOVAtest and continued with Duncan multiple range test with 95% confidence intervals.The results showed that (P.tetragonolobus (L.) DC.) which was planted in Ungaran has the optimum growth of legume.